UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR SISWA DALAM PEMBELAJARAN GEOMETRI MELALUI PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATIC EDUACTION - I Nyoman Darma; I Wayan Suandhi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Mahasaraswati Denpasar, 2011)
The learning model of realistics mathematics education (RME), which refers to social constructivism, providing opportunities for learners to explore and develop ideas. For the reason, the classroom action research was conducted with the aim to increase the learning activity and student achievement in learning geometry through the application of RME learning model in 5 grades of elementary students. It has been conducted through three cycles, and each cycle consists of three face-to-face activities in the classroom. Data on activity were collected by observation technique using a sheet of observation, while data of learning achievement were collected by testing learning outcomes. The results showed, from precycle the cycle I, the cycle I to II, and from II to III cycles, the tendency of increasing the students values in learning activities (21.56%, 18.76% and 17.24%), absorptive ability (217.25%, 9 , 54%, and 4.68%), and mastery learning (not defined, 24.09% and 38.46%). Thus, RME in geometry has increased, both activity and student learning achievement.